Entangled in fibers: a preliminary study of a great tit’s (Parus major) fatal encounter with anthropogenic nesting material - A. Winiewicz; W. Mierzejewska; M. Nartowicz; A. Syguła; A. Hryszko; L. Kabacińska; M. Karpiesiuk; J. Kościelniak; A. T. Dubis; K. Deoniziak (The European Zoological Journal)
Animals often incorporate anthropogenic materials into their nests, a behavior that is increasingly common as human activities expand and alter natural habitats. Although such behavior in birds is well documented, studies frequently overlook visual documentation of the nests and the chemical characterization of the anthropogenic materials used in their construction. This paper presents an observation of a single incubating female great tit (Parus major), a common urban dweller, that became fatally entangled in anthropogenic materials used for nest construction. We provide visual documentation of the nest, the bird carcass, and the observed anthropogenic waste, along with chemical characterization to identify its synthetic origin. During nest box maintenance in autumn 2023, anthropogenic materials were observed in 2 out of the 20 occupied nests. One nest was built with a mixture of natural and anthropogenic materials. A dead female bird was found on top, entangled by the leg in plastic fibers, along with six eggs. The fibers, observed in the nest cup surrounding the eggs, were red, purple, turquoise, and white, accounting for 2.68% of the total nest weight. Using Fourier transform infrared spectroscopy, we identified the fibers as polyester, polyamide, polypropylene, and nylon-polypropylene, which are common polymers in the textile industry. Our observations show how entanglement in anthropogenic materials used for nest construction can be detrimental to birds.